2016
DOI: 10.3390/cryst6110151
|View full text |Cite
|
Sign up to set email alerts
|

E’’ Raman Mode in Thermal Strain-Fractured CVD-MoS2

Abstract: Molybdenum disulfide (MoS 2 ) has recently attracted considerable interests due to its unique properties and potential applications. Chemical vapor deposition (CVD) method is used widely to grow large-area and high-quality MoS 2 single crystals. Here, we report our investigation on thermal strain-fractured (SF) single crystalline MoS 2 , oxidation-fractured MoS 2 , and normal MoS 2 by atomic force microscopy (AFM), Raman and photoluminescence (PL) measurements. Several new Raman modes are observed for SF-MoS 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…It was also shown that the nitrogen doping could be an effective way to produce hole doping in MoS 2 monolayers by creating N S acceptor defects. The presence of weak side peaks at about 409 and 378 cm −1 (see Figure (b)) also confirms a high defect concentration in our monolayer, because these peaks were previously assigned to the defect‐induced modes …”
Section: Resultssupporting
confidence: 82%
“…It was also shown that the nitrogen doping could be an effective way to produce hole doping in MoS 2 monolayers by creating N S acceptor defects. The presence of weak side peaks at about 409 and 378 cm −1 (see Figure (b)) also confirms a high defect concentration in our monolayer, because these peaks were previously assigned to the defect‐induced modes …”
Section: Resultssupporting
confidence: 82%
“…Two kinds of MoS 2 samples coexist in different shapes: broken triangle and 1D nanobelt. The inserted height profile along the green solid line in Figure a reveals that the flake is ∼1.0 nm‐thick while the nanobelt is ∼1.9 nm‐thick and 0.5 µm‐wide, indicating that the transferred MoS 2 nanobelt is bilayer . Intuitively, it is considered that bilayer MoS 2 formed on MoO 2 nanorods.…”
Section: Resultsmentioning
confidence: 99%
“…The Raman and PL intensities on MoS 2 nanoribbons are stronger and weaker than on MoS 2 flakes, respectively, indicating that such nanoribbons grow on flakes. AFM measurements exhibit that the number of layer of MoS 2 nanoribbons are 1–3 . STEM and SAED results confirm that such MoS 2 nanoribbons grow along MoS 2 true〈10true1¯0true〉 direction .…”
mentioning
confidence: 64%
“…Figure a shows the Raman spectra of MoS 2 nanoribbons (black) and bottom flakes (red), respectively. Two characteristic Raman peaks for MoS 2 , E 1 2g and A 1g , can be observed . It is well known that the frequency difference between E 1 2g and A 1g Raman peaks increases with the number of layer due to the interlayer van der Waals interaction and dielectric screening of the long range Coulombic interaction .…”
mentioning
confidence: 92%